Assessing the economic feasibility of assuring nutritionally adequate diets for vulnerable populations in Uttar Pradesh, India: Key findings from ‘cost of the diet’ analysis (OR21-05-19) - Kachwaha, Shivani; Nguyen, Phuong Hong; Defreese, Michelle; Cyriac, Shruthi; Girard, Aimee Webb; Avula, Rasmi; Menon, Purnima (Oxford University Press, 2019)
Uttar Pradesh (UP) is the most populous state with the highest burden of undernutrition in India. Alive & Thrive is working to strengthen behavior change communication (BCC) on diet diversity and quantity, using health systems platforms to deliver maternal nutrition intervention. However, evidence on the accessibility and affordability associated with recommended diets is limited. This study aims to: 1) examine the costs of nutritious foods in local markets, 2) identify inexpensive sources of essential micronutrients which could be promoted through BCC interventions.